Pressure Ulcers and Nutrients: From Established Evidence to Gaps in Knowledge - Kassym, Laura; Zhetmekova, Zhuldyz; Kussainova, Assiya; Semenova, Yuliya; Vetrova, Anastassiya; Nurzhan, Sholpan; Sarbassova, Gauhar; Akhmetova, Almira; Orazalina, Ainash; Uzbekova, Saltanat; Bjørklund, Geir (Current Medicinal Chemistry, 2025)
Pressure ulcers (PUs) are caused by continuous pressure or friction on the skin that damages tissue, especially over bony prominences. A critical factor in the development and progression of PUs is poor nutritional status, which often involves deficiencies in essential nutrients such as proteins, vitamins (A, C, D, E, K, and the B complex), and trace elements (including zinc, selenium, copper, iron, and manganese). These micronutrients are vital for effective wound healing, as they play significant roles in cellular repair, immune function, and tissue regeneration. Laboratory tests for serum albumin, prealbumin, transferrin, retinol-binding protein, and anthropometric measures like height, weight, and body mass index (BMI) are used to evaluate a patient's nutritional status. Screening tools such as the Mini Nutritional Assessment (MNA), Malnutrition Universal Screening Tool (MUST), LPZ questionnaire, and Subjective Global Assessment (SGA) are commonly employed. Emerging evidence from various studies, including in vitro, in vivo, and clinical trials, underscores the importance of personalized nutritional interventions in managing PUs. Unlike generic dietary plans, tailored nutrition that addresses the specific needs of individuals shows greater potential in promoting wound healing and improving clinical outcomes. This synthesis of existing research highlights the critical influence of micronutrients on the healing process of PUs. It suggests that a personalized approach to nutrition, which takes into account individual patient requirements and deficiencies, is likely to be more effective than a one-size-fits-all strategy in the management of these complex wounds.
Keywords: Pressure ulcers